Natural products as antivibrio agents: insight into the chemistry and biological activity. Issue 53 (1st December 2022) - Kasanah, Noer; Ulfah, Maria; Rowley, David C.
Abstract : Natural products provide chemical diversity of antivibrio compounds. Abstract : Vibriosis causes serious problems and economic loss in aquaculture and human health. Investigating natural products as antivibrio agents has gained more attention to combat vibriosis. The present review highlights the chemical diversity of antivibrio isolated from bacteria, fungi, plants, and marine organisms. Based on the study covering the literature from 1985–2021, the chemical diversity ranges from alkaloids, terpenoids, polyketides, sterols, and peptides. The mechanisms of action are included inhibiting growth, interfering with biofilm formation, and disrupting of quorum sensing. Relevant summaries focusing on the source organisms and the associated bioactivity of different chemical classes are also provided. Further research on in vivo studies, toxicity, and clinical is required for the application in aquaculture and human health.